(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This review evaluates the clinical potential of poly-L-lactic acid/beta-tricalcium phosphate (PLLA/-TCP 60%-40%) composite implants for the reconstruction of maxillofacial bone defects, focusing on translational evidence published between 2020 and 2025. The aim was to assess whether PLLA/-TCP composites represent a safe, effective, and biologically functional alternative to conventional bone grafts in craniofacial regeneration. A systematic analysis of the literature from PubMed, Scopus, Web of Science, and PMC was conducted, including in vitro studies, preclinical animal models, clinical case series, and patient- specific 3D-printed implant applications. Particular attention was given to extrusion-based additive manufacturing workflows and material parameters such as pore size, porosity, -TCP content, and processing conditions. The reviewed evidence indicates that PLLA/-TCP implants demonstrate high biocompatibility, pronounced osteoconductivity, and predictable biodegrada- tion profiles. Clinical outcomes in orbital, zygomatic, alveolar, and selected mandibular defects were favorable, with low complication rates and substantial bone regeneration observed within 4–8 months. However, limitations persist for large segmental defects and infection-associated reconstructions. Overall, PLLA/-TCP patient-specific implants show strong clinical promise for medium-sized maxillofacial defects, supporting their continued development and validation through long-term clinical studies and standardized manufacturing protocols.